2020
DOI: 10.1007/s11130-020-00848-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Subcritical Water and Microwave-Assisted Extraction Techniques Impact on the Phenolic Compounds and 5-Hydroxymethylfurfural Content in Pomegranate Peel

Abstract: Two environmentally friendly innovative extraction techniques -subcritical water (SWE) and microwave-assisted extraction (MAE) were applied for the extraction of phenolics from pomegranate peel. The impact of process conditions (SWE: temperature 100-220°C, extraction time 5-30 min; MAE: solvent water and 50% ethanol, irradiation power 470 and 800 W) on the quality of extracts in terms of the content of total phenolics, total flavonoids, major phenolic constituents (gallic acid, ellagic acid, punicalin, punical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Most experiments have proven that SBWE is superior to maceration, Soxhlet, and MAE [ 109 , 112 , 125 ], whereas Vladić et al concluded that the lower temperatures of SBWE are more convenient for the valorization of pomegranate peel and MAE is more efficient than SBWE for the extraction of phenolics from pomegranate peel while obtaining a 5-hydroxymethylfurfural-free extract [ 109 ].…”
Section: Compounds Extracted By Subcritical Watermentioning
confidence: 99%
“…Most experiments have proven that SBWE is superior to maceration, Soxhlet, and MAE [ 109 , 112 , 125 ], whereas Vladić et al concluded that the lower temperatures of SBWE are more convenient for the valorization of pomegranate peel and MAE is more efficient than SBWE for the extraction of phenolics from pomegranate peel while obtaining a 5-hydroxymethylfurfural-free extract [ 109 ].…”
Section: Compounds Extracted By Subcritical Watermentioning
confidence: 99%
“…Nevertheless, in the EOP aqueous extracts obtained in the BBD experiments, the concentrations of furfural and 5-hydroxymethylfurfural were lower than 0.012 g/L and 0.006 g/L, respectively. These values are very low with respect to another study on mandarin peels when subcritical water extraction was applied, which required more severe thermal conditions (130 °C, 20 min, 20% w / v ) [ 28 ]. Therefore, these results highlight the fact that the thermal degradation of the EOP carbohydrates was negligible under the tested MAWE conditions.…”
Section: Resultsmentioning
confidence: 73%
“…The thermal degradation of carbohydrates in foods, like xylose and glucose, generates the undesirable compounds furfural and 5-hydroxymethylfurfural, respectively [ 28 ]. At high concentrations, these degradation compounds can reduce the food quality [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results were compared with those obtained by UAE studied in a previous work by the same research team, concluding that the MW method presented a 1.7-fold higher yield after 4 min than after 10 min by UAE [ 58 ]. Regarding phenolic extraction, another study indicated that MAE (low MW power and 50% ethanol) was useful for phytochemical extraction [ 59 ]. Although there are relevant and promising results, they are nonunanimous and scarce.…”
Section: Pomegranate Peel Phenolic Compounds Extraction Techniquesmentioning
confidence: 99%